2008
DOI: 10.1111/j.1365-3156.2008.02013.x
|View full text |Cite
|
Sign up to set email alerts
|

Socio‐cultural, psychosexual and biomedical factors associated with genital symptoms experienced by men in rural India

Abstract: SummaryBiomedical, anthropological and psychiatric frameworks have been used to research different elements of men's sexual health -sexually transmitted infections, psychosexual concerns and psychological distress -but rarely within the same study. We combined these in a study in rural north India. In Tehri Garhwal and Agra districts, we explored male perceptions of genital and sexual symptoms through focus group discussions and then conducted a clinic-based survey of 366 symptomatic men who presented at rural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 28 publications
3
35
0
Order By: Relevance
“…Few previous studies conducted by Chaddha, et al, 14 Grover S, et al 15 and Gautam M, et al 16 reported that patients complaining of Dhat Syndrome are typically more likely to be young people, who are recently married or single; of average or low socio-economic status, coming from a rural area and belonging to a family with conservative attitudes towards sex while a study conducted by Verma R, et al 17 reported more prevalence from urban area.…”
Section: Discussionmentioning
confidence: 93%
“…Few previous studies conducted by Chaddha, et al, 14 Grover S, et al 15 and Gautam M, et al 16 reported that patients complaining of Dhat Syndrome are typically more likely to be young people, who are recently married or single; of average or low socio-economic status, coming from a rural area and belonging to a family with conservative attitudes towards sex while a study conducted by Verma R, et al 17 reported more prevalence from urban area.…”
Section: Discussionmentioning
confidence: 93%
“…Few previous studies conducted by Chaddha et al 12 , Grover S et al 13 and Gautam M et al 14 reported that patients complaining of Dhat Syndrome are typically more likely to be young people, who are recently married or single; of average or low socio-economic status, coming from a rural area and belonging to a family with conservative attitudes towards sex while a study conducted by Verma R et al 15 reported more prevalence from urban area…”
Section: Discussionmentioning
confidence: 96%
“…Misconceptions that semen loss is dangerous are still prevalent in our culture (Kendurkar Kaur, Agarwal, Singh, & Agarwal, 2008). Rural and illiterate people seek help from faith healers mainly 84 V. Agarwal and S. Mahapatra because of the non-availability of sex education, of shame and guilt associated with discussing sex and sexual problems with their family due to cultural inhibitions and because of advertisements by ayurvedic, unani or unqualified practitioners at rail or road approaches to cities offering cure to these problems (Gautham et al, 2008), which is what happened to the father of the patient.…”
Section: Discussionmentioning
confidence: 98%
“…Because of ignorance, guilt and shyness people seek help from local trusted faith healers, quacks and self-acclaimed sex specialists who are not trained or licensed, especially in rural India. These healers-through-advertisement recognize normal processes like nocturnal emissions as illness and propose cures that are likely to reinforce these myths and sexual misconceptions, rather than treating patients by providing correct information (Gautham et al, 2008;Schensul 2002). Such irrational help-seeking leads to stress and magnification of symptoms, which may further lead to psychiatric disorder.…”
Section: Introductionmentioning
confidence: 98%